PENGARUH PENAMBAHAN FITOIMUN® KE DALAM PAKAN TERHADAP PERTUMBUHAN KEPITING BAKAU (Scylla serrata) YANG DIPELIHARA DI TAMBAK SILVOFISHERY DESA SALO PALAI KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Wanda Rachmawati; Gina Septiani; Esti Handayani Hardi (Universitas Sriwijaya, 2022)
Mangrove crab (Scylla serrata) is a crab that has high potential and is cultivated in mangrove areas, so that many people keep mangrove crabs. However, there are still many obstacles, including slow growth. The purpose of this study was to examine the use of Fitoimun® mixed into crab feed to see survival, weight growth, specific daily growth rate, feed conversion ratio, and carapace width, which were reared in silvofishery ponds in Salo Palai Village. The study used a completely randomized design with 3 treatments and 3 replications. The treatment was Fitoimun® products containing Solanum ferox L and Boesenbergia pandurata, with a dose of 0 mL/kg, 20 mL/kg, 24 mL/kg. This study used mud crabs a weight of about 187-300 grams and a carapace width of about 95.0-110.5 mm. Feeding is given once every 2 days, in the morning at 07.00-08.00 and in the afternoon at 16.00-17.00. The feed given to crabs was measured as 5% of the crab's biomass weight. The results showed that the use of Fitoimun® products had no significant effect on survival, absolute weight growth, specific daily growth rate, carapace width, and feed conversion ratio, water quality during the study temperature 28.5°C, pH 7.5, DO 5.8 mg/L, salinity 13.8 mg/L pond. The relatively good Fitoimun® at a dose of 20 mL/kg mixed into mud crab (Scylla serrata) feed was able to increase growth, specific daily growth rate, feed conversion ratio, and carapace width. Keywords: Ftoimun®, growth survival, mud crab.